Biphasic Nanofibrous Constructs with Seeded Cell Layers for Osteochondral Repair - Jin, Guang-Zhen (Tissue Eng Part C Methods, 2014)
Biphasic scaffolds have gained increasing attention for the regeneration of osteochondral interfacial tissue because they are expected to effectively define the interfacial structure of tissue that comprises stratified cartilage with a degree of calcification. Here, we propose a biphasic nanofiber construct made of poly(lactide-co-caprolactone) (PLCL) and its mineralized form (mPLCL) populated with cells. Primary rat articular chondrocytes (ACs) and bone marrow-derived mesenchymal stem cells (MSCs) were cultured on the layers of bare PLCL and mPLCL nanofibers, respectively, for 7 days, and the biphasic cell–nanofiber construct was investigated at 4 weeks after implantation into nude mice. Before implantation, the ACs and MSCs grown on each layer of PLCL and mPLCL nanofibers exhibited phenotypes typical of chondrocytes and osteoblasts, respectively, under proper culture conditions, as analyzed by electron microscopy, histological staining, cell growth kinetics, and real-time polymerase chain reaction. The biphasic constructs also showed the development of a possible formation of cartilage and bone tissue in vivo. Results demonstrated that the cell-laden biphasic nanofiber constructs may be useful for the repair of osteochondral interfacial tissue structure.